Clinicopathological study of Ossifying fibroma - Rahman, Mohammad Asifur; Rahman, Tarin; Haider, Ismat Ara (Update Dental College Journal, 2019)
Ossifying fibroma is a benign neoplasm of bone and often considered a type of fibro-osseous lesion. It can affect both the mandible and the maxilla, particularly the mandible. Radiologically it presents as a mixed radiodense and radiolucent lesion that is well demarcated from normal bone and histopathologically it consists of highly cellular, fibrous tissue that contains varying amounts of calcified tissue resembling bone, cementum or both. The treatment consists in completely removing the lesion with curettage, surgical excision or en-block resection, depending on the size and location of the lesion. The aim of this study is to analyse the clinicopathological characteristics of ossifying fibroma and provide a proper management system. Materials and methods - The prospective study was performed in the Department of Oral & Maxillofacial surgery, Dhaka Dental College and Hospital, Dhaka, Bangladesh, from a period of January 2015 to January 2019. All patients were selected for this study based on clinical, radiological and histopathological confirmation of ossifying fibroma. The management of each case and follow-up data were documented. Result and observations - A total number of 25 patients of ossifying fibroma were selected for this study. The mean age of ossifying fibroma were 30.35 years with an age range 12 to 57 years. Female17 (57%) represented the majority of the affected patients and more common in the mandible (60%).The radiographic appearances of ossifying fibroma presented 17(68%) mixed type and 18(72%) well-defined borders. Bone expansion 19(76%), tooth displacement 09(36%) and root resorption 10(40%) were observed in ossifying fibroma. Surgical resection, enucleation and curettage were treatment of choice in ossifying fibroma. Conclusion - Ossifying fibroma occurs more commonly in women in the 2nd to 4th decade of life and presents a painless bony swelling and deformity in mandible and maxilla. Frequently it shows as a mixed radiographic image that is well demarcated from normal bone. The treatment consists in completely removing the lesion with curettage, surgical excision or en-block resection, depending on the size and location of the lesion in ossifying fibroma. Update Dent. Coll. j: 2019; 9 (2): 7-12